Dietary enzyme-hydrolyzed marine proteins supplementation could improve growth, protein metabolism and immune response in mud crab (Scylla paramamosain) - Tiantian Xu; Xiaoyue Li; Min Jin; Zheng Tang; Xishuai Cui; Yinzhao Zhang; Feng Tang; Qicun Zhou (Aquaculture Reports)
A feeding trial was conducted to evaluate the enzyme-hydrolyzed marine proteins (EMP, comprising fish protein peptides, enzymatic squid protein, and seaweed polysaccharides) supplementation on the growth performance, protein metabolism and immune responses of mud crabs (Scylla paramamosain). Four isonitrogenous and isolipidic diets were prepared with different treatments: a normal control (NC) containing 30 % FM, a positive control (PC) with 30 % FM supplemented with 2 % EMP, an experimental diet with 28 % FM and 1 % EMP (EMP1), and another experimental diet with 26 % FM and 2 % EMP (EMP2). A total of 120 healthy mud crabs were randomly assigned to individual crab apartments, with three replicates per treatment (10 crabs per replicate). Results showed that crabs given the EMP2 diet exhibited the highest PWG and SGR (P < 0.05). Crabs on the NC diet showed substantially decreased pepsin and amylase activities in the hepatopancreas and stomach compared to other diets (P < 0.05). Dietary EMP supplementation significantly upregulated the expression of molting-related genes (ecr, met, chi, e75, chh, and famet) in the hepatopancreas, protein metabolism-related genes (akt, rheb, tor, pi3k, irs, s6k, eif4e, 4ebp1, and 4ebp2) in both the hepatopancreas and intestines, and immune-related genes (lysozyme, proPO, toll, myd88, tube, pelle, traf6, imd, tak1, and relish) in the intestines (P < 0.05). In conclusion, dietary EMP supplementation enhances growth, promotes molting, and strengthens the innate immune response, demonstrating its potential as an alternative protein source and immune enhancer for mud crabs.